Implementasi Low Power System untuk Pengambilan dan Pengiriman Data Berdasarkan Kehadiran Manusia - Dewi Pusparini; Mochammad Hannats Hanafi Ichsan; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In this modern era, technological progress is growing rapidly for human needs, therefore it is very necessary to measure electrical energy. Therefore, a device is used to maintain environmental safety and to save the power. Low power implementation system for retrieving and sending data based on manusa configuration is a system that can be used for certain environments or only as a detection of human presence with low power usage, because the system will only activate human sensors. This system uses a pir sensor to detect human presence, and uses the VC0706 camera for the image capture process, then the image is stored on the sd card connected to the Ethernet module. By using the Arduino Uno microcontroller as a data processor produced both from the pir sensor and the camera. After this system retrieves image data, the data that is passed will be sent to people who want to know the condition of a particular place by accessing the IP address set in the Ethernet module to open the web browser page. The system is created by using the sleep mode low power method, where the compilation sensor does not detect anything, the data will automatically be finalized, using the sleep mode, the power saved is 0.010 amperes to 0.025 amperes.